The relationship between knowledge and self-efficacy of nurses regarding early initiation of cardiopulmonary resuscitation and automated defibrillation in Saudi Arabia - Zainah D Alaryani (Belitung Raya Foundation, 2021)
Background: Cardiopulmonary resuscitation (CPR) and early defibrillation are the most common procedures performed by nurses as the first responders to cardiac arrest patients in the hospital setting. Therefore, nurses are demanded to have high skills for effective performance. Self-efficacy and knowledge are considered significant factors affecting early initiation of CPR and automated defibrillation. However, previous studies mostly focused on nursing students instead of frontline nurses.